Volatility Modelling for Tourism Sector Stocks in Borsa Istanbul - Gençer Çelik, Gülşah (International Journal of Economics and Financial Issues, 2020)
This paper examines the volatility of the tourism sector in Borsa İstanbul in Turkey, paying special attention to the role of exchange rate exposure in the process. The GARCH, BJR (TARCH) and EGARCH models are employed to estimate the volatility in the stock returns of Turkish tourism firms using daily data from 02 January 2002 to 13 April 2020. The results suggest that: (i) compared to the GARCH and GJR model results, the EGARCH model provides valuable information on the volatility of returns in tourism sector and on the impact of exchange rate on stock returns; (ii) the impact of exchange rate risk on stock returns is significant and positive for 3 tourism firms and negative for 2 firms; (iii) the findings on volatility of stock returns indicate that the time-dependent components of volatility is clearly more important than the time-independent component of volatility in predicting current volatility; (iv) the volatility of stock returns are highly persistent and the volatility at time t is more sensitive to past period volatility than past surprises in the market; (v) surprisingly, while there is no leverage effect, shocks have asymmetric effect on volatility implying that the impact of negative news do not outweigh positive news (or the impact of positive news on volatility is higher than the impact of negative news in the market). Keywords: Turkish Tourism Industry; Volatility; Foreign Exchange Rate Risk; Stock Returns; ARMA, GARCH; GJR(TARCH); EGARCH Model JEL Classifications: G1, N2, C5 DOI: https://doi.org/10.32479/ijefi.9811